The influence of rotation and viscosity on generalized conformable fractional micropolar thermoelasticity with two temperatures - El-Sapa, Shreen; El-Bary, Alaa A.; Atef, H. M. (Frontiers in Physics, 2023)
This research paper presents the generalized micropolar thermo-visco-elasticity model in an isotropic elastic medium that has two temperatures with conformable fractional order theory. The whole elastic medium rotates at a constant angular velocity. The generalized theory of thermoelasticity with one relaxation time is used to describe this model. We aim to study the effect of conformable fractional derivative, effect of rotation, and the two-temperature coefficients. The normal mode analysis is used to acquire the specific articulations for each component under consideration. Moreover, some specific cases are discussed with regarding to the problem. Numerical findings are gathered and displayed graphically for the variables under consideration. The outcomes were analyzed in terms of the presence or absence of rotation, viscosity, conformable fractional parameter and two temperatures for various values.